Assessing the Relationship Between Transformational and Transactional Leadership Styles and Employee Perfomance: A Case Study Among Event Staff at Inner Sanctum Services - Sukma Murni, Ab Hadi (2012)
Leadership is a vital issue in every organization primarily because the decisions made by the leaders could lead to success or business failure. The main purpose of this research is to examine the relationship between transformational and transactional leadership styles and employee performance among the event staff at Inner Sanctum Services. It is crucial for the management of Inner Sanctum Services to identify which leadership styles could enhance their employee performance and additionally, to understand the extent of such influence as well. Thus, the objectives of this research are twofold (i) to examine the relationship between transformational leadership style and employee performance at Inner Sanctum Services (ii) to examine the relationship between transactional leadership style and employee performance at Inner Sanctum Services. In assessing the relationship between the variables, a total of 69 questionnaires were distributed, completed and analysed using descriptive and inferential data analysis technique. The findings of this research reveal that both transformational and transactional leadership styles have positive relationship with employee performance. However, transformational leadership has significant influence on employee performance and further recommendations are made at the end of this research.